Is the asset transfer of public leisure facilities in England an example of associative democracy? - Geoff Nichols; Deborah Forbes; Lindsay Findlay-King; Gordon Macfadyen (Administrative Sciences, 2015)
In England, public sports facilities and libraries provided by local government are being transferred to management and delivery by volunteers. The catalyst for this development has been reductions in local government budgets. However, case studies explore if this asset transfer "offers a way of restoring the ideal of committed public service in the face of widespread bureaucratic failure and retreat", as a form of associative democracy and empowerment of both the volunteers and those for whom the services are provided.
Keywords: 350; associative democracy; public provision; leisure services; volunteers